Fourier Transformed Infrared (FTIR) spectroscopy analysis of patchouli essential oils based on different geographical area in Aceh. Issue 1 (February 2021) - Sufriadi, E; Meilina, H; Munawar, A A; Idroes, R
Abstract: Studies on the quality difference between oils in various provinces have been conducted with varied results, especially between Acehnese Patchouli and Javanese Patchouli. However, studies on quality differences of Acehnese Patchouli based on geographic differences have never been carried out, thus, still leaving a big mystery in determining whether geographical differences such as coordinates and height from sea level produce different quality. The purpose of this study was to determine the effect of geographic location (coordinates and height of water MASL) of the patchouli cultivations on oil quality by conducting Principal Component Analysis (PCA) on the FTIR spectrum of patchouli oil from 3 different districts, namely South Aceh, Aceh Tamiang and South-West Aceh. The results indicate a water content difference as it is close to the O-H group wave number, which usually indicates the presence of Patchouli alcohol. The PCA analysis results show that there is a very significant difference between patchouli oil from South Aceh and Aceh Tamiang and South-West Aceh, caused by the height and patchouli variety difference. The PCA method validation is also quite reliable, which is proven by an explained variance plot.